Opportunities and barriers to the development of Islamic banking in the global economy - Melon, Patrycja (Contemporary trends in business security: Problems and challenges of eastern economies, 2022)
Islam is one of the largest religion in the world, from which the genesis of Islamic banking derives. The main set of the rules and norms that define all aspects of Muslim life is Sharia. Islamic financial institutions operate according to the principles of Shariah. The purpose of this article is to characterize Islamic banking: foundations, financing methods and to define opportunities and threats associated with the development of Islamic banking in the global economy. Islamic banking is based on certain principles. The most important principle is the prohibition of riba, meaning the inability to collect interest on loans. Business entities are also not allowed to engage in speculative operations and anti-social investments. The article presents the main instruments of Islamic banking: mudaraba, musharaka and murabaha. Interest in Islamic banking has increased over the decade. However, it is still a small sector in the global economy.